2016
DOI: 10.1016/j.foodchem.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pecan phenolics on the release of nitric oxide from murine RAW 264.7 macrophage cells

Abstract: Inflammation is linked to numerous chronic disease states. Phenolic compounds have attracted attention because a number of these compounds possess anti-inflammatory properties. A phenolic crude extract was prepared from pecans and separated by Sephadex LH-20 column chromatography into low- and high-molecular-weight (LMW/HMW) fractions. Anti-inflammatory properties of these fractions were assessed in LPS-stimulated RAW 264.7 murine macrophage cells. NO and reactive oxygen species (ROS) production was monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Each treatment was performed in six replicates in a single experiment. The production of nitric oxide (NO) was measured using the Griess reaction [ 18 ]. Evaluation of the concentration of the cytokines released (TNF-α, IL-1β, IL-6, and IL-10) in the supernatants of the RAW 264.7 cell culture was carried out with enzyme-linked immunosorbent assay kits (ELISA MAX Deluxe Set) (Biolegend Inc., San Diego, CA, USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Each treatment was performed in six replicates in a single experiment. The production of nitric oxide (NO) was measured using the Griess reaction [ 18 ]. Evaluation of the concentration of the cytokines released (TNF-α, IL-1β, IL-6, and IL-10) in the supernatants of the RAW 264.7 cell culture was carried out with enzyme-linked immunosorbent assay kits (ELISA MAX Deluxe Set) (Biolegend Inc., San Diego, CA, USA) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A crude extract and its low-and high-molecular weight fractions (LMW and HMW, respectively) were evaluated as anti-inflammatory on LPS-stimulated murine RAW 264.7 macrophages, under three different conditions: a) co-incubation of LPS and pecan extracts, b) pre-incubation of the cells with LPS, and c) preincubation of the cells with pecan extracts (Robbins et al, 2016). Results showed that LMW fraction exhibited a dose dependent reduction of NO and ROS production when cells were co-incubated with LPS and extract or when pre-incubated with LPS prior to extract, however, no anti-inflammatory effect was observed with the crude extract or the HMW fraction, indicating that phenolic acids and small tannins found in the LMW fraction exerted this antiinflammatory activity, probably by quenching ROS involved in the activation of NF-κB.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Through their antioxidant property, flavonoids could potentially prevent free-radical-related injury. They are able to scavenge a wide range of reactive oxygen (ROS), nitrogen (NO) and chlorine species [ 11 , 12 , 13 ] as well as inhibit the production of reactive species [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%